2015
DOI: 10.1590/0037-8682-0312-2014
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of reported cases of acute Chagas disease in the State of Pernambuco, Brazil, from 2002 to 2013

Abstract: Introduction: Control strategies to eliminate the transmission of Chagas disease by insect vectors have signifi cantly decreased the number of reported acute cases in Brazil. However, data regarding the incidence and distribution of acute Chagas disease cases in the State of Pernambuco are unavailable in the literature. Methods: A geographical information system was used to delineate the spatiotemporal distribution profi le of the cases from 2002 to 2013 in 185 municipalities of Pernambuco based on the municip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, as previously mentioned, the Southern Cone Initiative has changed the epidemiological profile of the disease, as the country has received international certification for the interruption of vectorial transmission by T. infestans in 2006. In fact, a study carried out in Pernambuco state showed a significant decrease in new cases starting in 2006 [ 25 ]. Because of the decrease in vectorial transmission in Brazil, attention should be directed to the new cases that occur through contaminated food and beverages in endemic areas [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as previously mentioned, the Southern Cone Initiative has changed the epidemiological profile of the disease, as the country has received international certification for the interruption of vectorial transmission by T. infestans in 2006. In fact, a study carried out in Pernambuco state showed a significant decrease in new cases starting in 2006 [ 25 ]. Because of the decrease in vectorial transmission in Brazil, attention should be directed to the new cases that occur through contaminated food and beverages in endemic areas [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the distribution of NTDs in endemic areas is fundamental to the follow-up and assessment of interventions and the effectiveness of control measures. Attention has recently turned to epidemiological studies considering the spatial distribution of NTDs in the general population [ 25 28 ]. Owing to the scarcity of information describing NTDs in Brazilian children and adolescents, the epidemiological aspects and distribution of visceral and cutaneous leishmaniasis, acute Chagas disease, malaria, and schistosomiasis in individuals aged up to 19 years reported in the Health Notification Aggravation Information System (SINAN) database from 2009 to 2013 were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The present study found a high number of cases among individuals of productive age (15–59 years), suggesting increased frequency of exposure in this population due to occupational activities that increase the risk of transmission [ 23 ]. In the Brazilian Northeast macroregion, this age group was associated with a high number of cases arising from vectorial transmission, possibly due to frequent triatomine exposure of this rural population during work-related activities [ 24 26 ]. This finding is relevant as morbidity and mortality in acute CD is directly associated with reduced quality of life in infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, there was a high rate of T. cruzi oral transmission, and it has become increasingly frequent in this region, when compared to previous research. In other regions, where oral transmission by T. cruzi is less frequent, for example, in the state of Pernambuco, this route of transmission has significantly decreased after 2006, a period in which Brazil received an international certificate for interrupting vector transmission by Triatoma infestans 24 .…”
Section: Discussionmentioning
confidence: 99%